A cost-benefit analysis of ecosystem services from restoring degraded soils to forest ecosystems in the Sahel - Sibiry Albert Kaboré; Emmanuelle Quillérou; Stéphanie Maiga-Yaleu; Maguette Kairé; Ibrahim Bouzou Moussa; Oumarou Malam Issa; Damien Hauswirth; Hassan Bismarck Nacro (Journal for Nature Conservation, 2024)

The pervasive and multifaceted influence of biocrusts on water in the world's drylands - David J. Eldridge; Sasha Reed; Samantha K. Travers; Matthew A. Bowker; Fernando T. Maestre; Jingyi Ding; Caroline Havrilla; Emilio Rodriguez‐Caballero; Nichole Barger; Bettina Weber; Anita Antoninka; Jayne Belnap; et al. (Global Change Biology, 2020)
The capture and use of water are critically important in drylands, which collectively constitute Earth's largest biome. Drylands will likely experience lower and more unreliable rainfall as climatic conditions change over the next century. Dryland soils support a rich community of microphytic organisms (biocrusts), which are critically important because they regulate the delivery and retention of water. Yet despite their hydrological significance, a global synthesis of their effects on hydrology is lacking. We synthesized 2,997 observations from 109 publications to explore how biocrusts affected five hydrological processes (times to ponding and runoff, early [sorptivity] and final [infiltration] stages of water flow into soil, and the rate or volume of runoff) and two hydrological outcomes (moisture storage, sediment production). We found that increasing biocrust cover reduced the time for water to pond on the surface (−40%) and commence runoff (−33%), and reduced infiltration (−34%) and sediment production (−68%). Greater biocrust cover had no significant effect on sorptivity or runoff rate/amount, but increased moisture storage (+14%). Infiltration declined most (−56%) at fine scales, and moisture storage was greatest (+36%) at large scales. Effects of biocrust type (cyanobacteria, lichen, moss, mixed), soil texture (sand, loam, clay), and climatic zone (arid, semiarid, dry subhumid) were nuanced. Our synthesis provides novel insights into the magnitude, processes, and contexts of biocrust effects in drylands. This information is critical to improve our capacity to manage dwindling dryland water supplies as Earth becomes hotter and drier.

Effects of the inoculation of cyanobacteria on the microstructure and the structural stability of a tropical soil - Oumarou Malam Issa; Christian Défarge; Yves Le Bissonnais; Béatrice Marin; Odile Duval; Ary Bruand; Luigi Paolo D’Acqui; Sofie Nordenberg; Marcus Annerman (Plant and Soil, 2007)